2014
DOI: 10.1093/annonc/mdu370
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of stereotactic body radiotherapy to primary tumor and metastatic locations in oligometastatic nonsmall-cell lung cancer patients

Abstract: SBRT to all disease sites, primary tumor and metastatic locations, in oligometastatic NSCLC patients produced an acceptable median PFS of 11.2 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 18 publications
7
110
0
2
Order By: Relevance
“…Patients were included if they had fewer than or equal to five metastases at the time of SBRT with at least one treated site being a lymph node. Although there are variable definitions of oligometastatic disease, fewer than or equal to five metastases was used in this study, as this is consistent with the definition used in many published series and a recent international clinical trial [1315]. The diagnosis of oligometastatic disease was based on clinical examination and imaging studies, preferably by positron emission tomography/computed tomography (PET/CT) scan although imaging with CT alone or MRI was permitted.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were included if they had fewer than or equal to five metastases at the time of SBRT with at least one treated site being a lymph node. Although there are variable definitions of oligometastatic disease, fewer than or equal to five metastases was used in this study, as this is consistent with the definition used in many published series and a recent international clinical trial [1315]. The diagnosis of oligometastatic disease was based on clinical examination and imaging studies, preferably by positron emission tomography/computed tomography (PET/CT) scan although imaging with CT alone or MRI was permitted.…”
Section: Methodsmentioning
confidence: 99%
“…We considered all the reports presenting data about oligometastatic NSCLC patients with brain metastases. We excluded the studies enrolling patients with various tumor types (8,(11)(12)(13)27,(29)(30)(31)(32)(33)(34). As reported in Table 2, literature data are available from case reports, retrospective series and phase II trials.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that local control rates can reach 85normal%90normal% after SBRT for early stage lung cancer, which is almost equal to surgery alone 1 , 2 . Up to now, the clinical application of SBRT has been extended to oligometastatic lung tumors and other types of malignancies, such as liver cancer and pancreatic cancer 4 , 5 , 6 . However, the implementation of SBRT technique is a great concern for its single high dose irradiated to target volume within a short time.…”
Section: Introductionmentioning
confidence: 99%